Odpowiedź:
Cześć :)
a) [tex]\sqrt{4} (x+4x^{0}) = \sqrt{16}-x[/tex]
potęga 0 - zawsze daje w wyniku 1
2(x+1) = 4 - x
3x=6
x=2
b) [tex]\frac{x}{\sqrt{36} } +\sqrt{2}^{2}=\frac{x+3x^{0}}{\sqrt{9} } -x[/tex]
[tex]\frac{x}{6} +2 = \frac{x+1}{3} - x[/tex]
[tex]\frac{x}{6}-\frac{x+1}{3} +x = -2[/tex] - Mnożymy 6* obie strony
x - 2x + 2 + 6x = -12
5x -2 = -12
5x = -10
x= -2
c) [tex]\frac{x+6^{0} }{3} - \frac{2(-9^{0}+x)}{\sqrt{81} } = \frac{3^{0}}{\sqrt{9}} - \frac{x}{3^{2}}[/tex]
[tex]\frac{x+1}{3}- \frac{2+2x}{9} = \frac{1}{3} - \frac{x}{9}[/tex] <- mnożymy 9 * obie strony
3x+3-2x+2= 3 - x
2x = 8
x = 4
Pozdrawiam, miłego dzionka